2021
DOI: 10.1002/adma.202102473
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Off‐Equilibrium Morphing Pathways of a Supramolecular Shape‐Memory Polymer

Abstract: SMP) can only switch monotonically between its temporary and permanent shapes. Advanced hydrogels [11][12][13] incorporating distinct hydrogel components in a composite manner allow access to much more sophisticated shape-shifting behaviors such as reversible buckling. However, the behavior typically requires complex external triggering, for example, two/ more different stimuli. Similarly, multi-SMP capable of complex shifting amongst more than two shapes demands access to multi-step temperature control in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…3b). [46][47][48][49] Analogously, a shape memory polybenzoxazine lm consisting of arylamine mannich-type linkage was synthesized, whose chemical structure is different from that of the conventional polybenzoxazines. 50 Mannich polybenzoxazines possessed more weak hydrogen bonds of -OH/p that only existed at relatively lower temperatures and served as the responsive switch.…”
Section: Smps Based On Physical Switchesmentioning
confidence: 99%
“…3b). [46][47][48][49] Analogously, a shape memory polybenzoxazine lm consisting of arylamine mannich-type linkage was synthesized, whose chemical structure is different from that of the conventional polybenzoxazines. 50 Mannich polybenzoxazines possessed more weak hydrogen bonds of -OH/p that only existed at relatively lower temperatures and served as the responsive switch.…”
Section: Smps Based On Physical Switchesmentioning
confidence: 99%
“…[ 17–21 ] Fascinating material properties arise from disrupting the equilibrium state of dynamic bonding, for example: polymers with spiropyran go through force‐induced covalent‐bond activation and give rise to visible color and fluorescence; supramolecular polymers containing metal–ligand motifs can self‐heal by exposing to ultraviolet irradiation; and polymers functionalized by self‐complementary hydrogen bonded ureidopyrimidinone (UPy) moieties shows shape‐memory effect through temperature change. [ 22–24 ] Among these options, metal–ligand coordination bonding is particularly appealing to realize a particular desired response, because of the ease of tuning the stability of the bond.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Fascinating material properties arise from disrupting the equilibrium state of dynamic bonding, for example: polymers with spiropyran go through force-induced covalent-bond activation and give rise to visible color and fluorescence; supramolecular polymers containing metal-ligand motifs can self-heal by exposing to ultraviolet irradiation; and polymers functionalized by self-complementary hydrogen bonded ureidopyrimidinone (UPy) moieties shows shape-memory effect through temperature change. [22][23][24] Among these options, metal-ligand coordination bonding is particularly appealing to realize a particular desired response, because of the ease of tuning the stability of the bond.One of the most popular polymers for fabricating sensors and actuators is polydimethylsiloxane (PDMS). [2,7] It commonly serves as an essential substrate or a responsive component due to the attractive physical and chemical properties, including low Polymers are at the core of emerging flexible sensor and soft actuator technology.…”
mentioning
confidence: 99%
“…For example, Xie et al have demonstrated many wonderful works on SMPs, especially in the direction of photopolymerizable SMPs. [2][3][4] The rational use of methods such as optimizing 3D printing schemes and ingenious design of polymer components have realized the rapid and efficient preparation of multifunctional reversible shape memory devices. Without changing the equipment, the printing speed of 3D printing can be increased by order of magnitude to 400 mm h -1 by introducing the hydrogel interface.…”
Section: Introductionmentioning
confidence: 99%